Design and development of application for post-stroke aphasia using user-centred design approach - Muhammad Hafis, 1995-, author 611819 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik dan Multimedia))